Penerapan Strategi Pemasaran Digital Pada UMKM Kopi Murni Pak Tuwo Sebagai Upaya Peningkatan Penjualan Produk - Khairunnisa Rosyadah; Ira Wikartika (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Kuliah Kerja Nyata (KKN) Tematik activities are a form of community service carried out by a group of students to help solve problems that exist in an area without expecting anything in return and aiming to achieve equitable development. This service activity aims to empower MSME actors in the digitalization era to achieve maximum results. Creativity and innovation are needed to create opportunities for business actors to increase people's purchasing power. For this reason, the Thematic KKN activities were carried out by Universitas Pembangunan Nasional “Veteran” Jawa Timur students for one of the MSMEs in Pulosari Village, Bareng District, Jombang Regency, namely Kopi Murni Pak Tuwo. This activity aims to increase MSMEs understanding of digital marketing as an effort to develop businesses with good product marketing achievements. The implementation method uses the FGD (Focus Group Discussion) method with MSMEs actors Kopi Murni Pak Tuwo. The results of this activity are increased literacy related to digital marketing for the owner of MSMEs Kopi Murni Pak Tuwo and wide market reach that influences the increase in product sales.